Preferential and synergistic arsenate–phosphate retention by porous biochar revealed by depth profiling X-ray photoelectron spectroscopy - Junho Han; Seoyeon Lee; Minhee Kim (Journal of Environmental Chemical Engineering, 2026)

How long will perfluoroalkyl substances persist in sludge-amended soils?: Century-scale regional accumulation-decay modeling for North America, Europe, and Asia - Minhee Kim; Seunghun Hyun; Junho Han (Journal of Hazardous Materials, 2026)

Asymmetric molecular design of buried interfaces for efficient perovskite solar cells - Minhee Kim; Seungwook Choi; Jiheon Lim; Ju Yong Han; Ana Jang; Yul Hui Shim; Jinhyun Kim (Chemical Engineering Journal, 2026)

Catalytic activation of peracetic acid with tungsten–modified iron oxides for decomposing pharmaceuticals in water - Chaejin Choi; Ayoung Choi; Haesung Lee; Minhee Kim; Noor S. Shah; Javed Ali Khan; Mallikarjuna N. Nadagouda; Changseok Han (Chemical Engineering Journal, 2026)

Historical and future water quality risks driven by climate change: Strategic management and overcoming challenges - Minhee Kim; Min Jang; Choe Earn Choong; Junho Han (Water Research, 2026)

Digestive ripening and fragmentation of goethite nanorods into nanospheres under natural wet-dry cycles: Unveiling hidden nanocolloid mobilization to water system - Junho Han; Evert J. Elzinga; Minhee Kim (Water Research, 2025)

Molybdenum-modified iron oxides mediated enhanced degradation of meropenem by peroxydisulfate - Gwangmin Kim; Ayoung Choi; Haesung Lee; Libor Machala; Minhee Kim; Pinelopi P. Falara; Michaela Polaskova; Petr Novak; Nikolaos Ioannidis; George Mitrikas; Virender K. Sharma; Mallikarjuna N. Nadagouda; et al. (Chemical Engineering Journal, 2025)

Integrating bioaccessibility into human health risk assessment: Stabilization approach of smelter-contaminated soil with natural organic amendments - Minhee Kim; Jong-Sung Kim; Hee-Myong Ro; Junho Han (Journal of Environmental Management, 2025)

Feasibility of gold leaching from waste printed circuit boards with an airlift bioreactor applying the condensed distillers solubles as a microbial nutrient and its recovery by reduction - Duy Tho Tran; Ngoc Tu Trinh Tran; Xiaoyu Lin; Jong-won Choi; Minhee Han; Myung-Hee Song; Yeoung-Sang Yun (Journal of Environmental Management, 2025)

Degradation of carbaryl by UV/chlorine process: Optimal degradation conditions, reaction intermediates, and mechanisms - Ayoung Choi; Jungyeon Kim; Haesung Lee; Minhee Kim; Xi-Zhi Niu; Bineyam Mezgebe; Mallikarjuna N. Nadagouda; Abdulaziz Al-Anazi; Changseok Han (Chemical Engineering Journal, 2025)

Phosphate sorption mechanisms in biochar: Insights from depth profiling of porous structure across pH and pyrolysis conditions - Junho Han; Seoyeon Lee; Seunghun Hyun; Minhee Kim (Bioresource Technology, 2025)

Development of tungsten-modified iron oxides to decompose an over-the-counter painkiller, Acetaminophen by activating peroxymonosulfate - Aebin Sin; Libor Machala; Minhee Kim; Zdeněk Baďura; Martin Petr; Michaela Polaskova; Petr Novak; Mallikarjuna N. Nadagouda; Dionysios D. Dionysiou; Changseok Han (Science of The Total Environment, 2024)

Causative mechanisms limiting the removal efficiency of short-chain per- and polyfluoroalkyl substances (PFAS) by activated carbon - Junho Han; Choe Earn Choong; Min Jang; Junghee Lee; Seunghun Hyun; Won-Seok Lee; Minhee Kim (Chemosphere, 2024)

Treatment techniques for removal of polybrominated diphenyl ethers (PBDEs) from real wastewater: Limitations, challenges, and future research directions - Minhee Kim; Junho Han (Journal of Water Process Engineering, 2024)

Synergistic effect of climate change and water management: Historical and future soil salinity in the Kur-Araz lowland, Azerbaijan - Junho Han; Minhee Kim; Zaman Mammadov; Seoyeon Lee; Evert J. Elzinga; Garib Mammadov; Wonjae Hwang; Hee-Myong Ro (Science of The Total Environment, 2024)

Investigation on the adsorption characteristics of pharmaceuticals and personal care products on polyethylenimine-alginate-activated carbon composite fiber - Se-Been Mun; Minhee Han; Yub Raj Dangi; Bo-Gyeon Cho; Se-Ra Jin; Kwan-Yong Lee; Che-Ryong Lim; Chul-Woong Cho; Yeoung-Sang Yun (Desalination, 2023)

High-capacity/high-rate hybrid column for high-performance ion exchange - Sung Il Yoon; Minhee Han; Haribandhu Chaudhuri; Yeoung-Sang Yun (Environmental Research, 2023)

Correction to: No prominent toxicity of polyethylene microplastics observed in neonatal mice following intratracheal instillation to dams during gestational and neonatal period - YoungHoon Han; YoungMin Song; Geun Woo Kim; ChangSu Ha; JiSun Lee; MinHee Kim; HyeYoung Son; GiYong Lee; Ravi Gautam; Yong Heo (Toxicological Research, 2022)

No prominent toxicity of polyethylene microplastics observed in neonatal mice following intratracheal instillation to dams during gestational and neonatal period - YoungHoon Han; YoungMin Song; Geun Woo Kim; ChangSu Ha; JiSun Lee; MinHee Kim; HyeYoung Son; GiYong Lee; Ravi Gautam; Yong Heo (Toxicological Research, 2021)

Spatial distribution of salinity and heavy metals in surface soils on the Mugan Plain, the Republic of Azerbaijan - Junho Han; Zaman Mammadov; Minhee Kim; Elton Mammadov; Seoyeon Lee; Jisuk Park; Garib Mammadov; Guliyev Elovsat; Hee-Myong Ro (Environmental Monitoring and Assessment, 2021)

Adsorptive removal of cationic tricyclic antidepressants using cation-exchange resin - Jong-Won Choi; John Kwame Bediako; Yufeng Zhao; Shuo Lin; Amit Kumar Sarkar; Minhee Han; Myung-Hee Song; Chul-Woong Cho; Yeoung-Sang Yun (Environmental Science and Pollution Research, 2020)

Factors modifying the structural configuration of oxyanions and organic acids adsorbed on iron (hydr)oxides in soils. A review - Junho Han; Minhee Kim; Hee-Myong Ro (Environmental Chemistry Letters, 2020)
Oxyanions are ubiquitous in soils, organisms and the environment. Due to their unique chemical structure, oxyanions can be easily transferred into other systems. Carbonate (CO 3 2− ), nitrate (NO 3 − ), phosphate (PO 4 3− ), silicate (SiO 4 2− ) and sulfate (SO 4 2− ) are the major oxyanions in organisms and the soil environment, whereas arsenate (AsO 4 3− ), antimonate (SbO 4 3− ), borate (BO 3 3− ), selenate (SeO 4 2− ), and tellurate (TeO 4 2− ) are generally reported as toxic chemicals found at trace levels. Excessive oxyanions leached from soils into water have caused severe environmental problems. Here, we review the factors affecting the structural configuration of oxyanions and organic acids adsorbed on iron oxides and hydroxides. The configuration of oxyanions on iron (hydr)oxides is controlled by surface loading, pH, sample phase, competing ions and organic acids. Under conditions of low surface loading and low pH at the interface in the absence of competing ions, oxyanions with high affinity possibly form a complex with higher denticity. But an increase in pH decreases the number of sorption sites; thus, a transition from a tri- or bidentate complex to monodentate and outer-sphere complexes occurs.

Chemical extractability of As and Pb from soils across long-term abandoned metallic mine sites in Korea and their phytoavailability assessed by Brassica juncea - Junho Han; Juhee Kim; Minhee Kim; Deok Hyun Moon; Jung-Suk Sung; Seunghun Hyun (Environmental Science and Pollution Research, 2015)